2015
DOI: 10.1242/jeb.109108
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of basal deuterostome nervous systems

Abstract: Understanding the evolution of deuterostome nervous systems has been complicated by the ambiguous phylogenetic position of the Xenocoelomorpha (Xenoturbellids, acoel flat worms, nemertodermatids), which has been placed either as basal bilaterians, basal deuterostomes or as a sister group to the hemichordate/ echinoderm clade (Ambulacraria), which is a sister group of the Chordata. None of these groups has a single longitudinal nerve cord and a brain. A further complication is that echinoderm nerve cords are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 53 publications
0
32
1
Order By: Relevance
“…Previous studies using gene markers have shown that the developing amphioxus CNS displays marked spatial molecular heterogeneity at different developmental stages ([61,97,102,108112] and see S1 Table). However, most of these studies focused on individual genes across diverse developmental time points, making it difficult to precisely compare the relative positions of their expression patterns and to elaborate a unified map.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using gene markers have shown that the developing amphioxus CNS displays marked spatial molecular heterogeneity at different developmental stages ([61,97,102,108112] and see S1 Table). However, most of these studies focused on individual genes across diverse developmental time points, making it difficult to precisely compare the relative positions of their expression patterns and to elaborate a unified map.…”
Section: Discussionmentioning
confidence: 99%
“…The rest of the BNS remained on the ventral side of the body in protostomes (annelids, mollusks, arthropods, etc. ), but in our branch, the deuterostomes, the body inverted such that the entire nervous system now became dorsally oriented and separate from the mouth and digestive tract (Holland, 2015; Lowe et al, 2006). Finally, in chordates, the nervous system folded inward into the body, forming what defines the basic neural plan to the present day (Nieuwenhuys & Puelles, 2016), as is shown in the inset of Fig.…”
Section: Elaboration Of Behavior Along the Vertebrate Lineagementioning
confidence: 91%
“…Echinoderms, together with hemichordates, form the ambulacrarians, which along with the chordates constitute the deuterostomes (Cannon et al, 2014; Satoh, Rokhsar, & Nishikawa, 2014). Although there is little doubt that the last common ancestor of chordates featured a centralized nervous system (Holland, 2015a), the reconstruction of the ancestral deuterostome nervous system is much less straightforward (Holland, 2015b; Lowe, Clarke, Medeiros, Rokhsar, & Gerhart, 2015). In particular, interpretations of hemichordate data have proven to be polarized (Kaul‐Strehlow, Urata, Minokawa, Stach, & Wanninger, 2015; Lowe et al, 2003; Nomaksteinsky et al, 2009), and the current lack of information on the evolutionary diversification of echinoderm nervous systems further complicates this issue (Formery, Schubert, & Croce, 2019; Holland, 2015b; Nakano et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is little doubt that the last common ancestor of chordates featured a centralized nervous system (Holland, 2015a), the reconstruction of the ancestral deuterostome nervous system is much less straightforward (Holland, 2015b; Lowe, Clarke, Medeiros, Rokhsar, & Gerhart, 2015). In particular, interpretations of hemichordate data have proven to be polarized (Kaul‐Strehlow, Urata, Minokawa, Stach, & Wanninger, 2015; Lowe et al, 2003; Nomaksteinsky et al, 2009), and the current lack of information on the evolutionary diversification of echinoderm nervous systems further complicates this issue (Formery, Schubert, & Croce, 2019; Holland, 2015b; Nakano et al, 2006). Additional information on the basic architecture of the adult nervous system of key representatives of different echinoderm classes, involving contemporary imaging approaches and a broad selection of markers, is thus needed to establish a comparative framework and enable novel evolutionary inferences.…”
Section: Introductionmentioning
confidence: 99%